Application of Titanium Dioxide - Janus, Magdalena (IntechOpen, 2017)
Titanium dioxide is mainly used as a pigment and photocatalyst. It is possible to find it in food, cosmetics, building materials, electric devices, and others. This book contains chapters about application of titanium dioxide in different branches of economy such as the agriculture, the food industry, the medicine, the cosmetics, the water treatment technologies, and the semiconductors.